The impact of policy on availability and price of low‐price medicines in public healthcare institutions: A retrospective survey in Nanjing, China. (30th November 2021) - Zhu, Yulei; Ren, Yuqin; Wang, Hui; Fang, Wenqing; Xu, Xinglu; Wang, Ying; Dai, Huizhen; Li, Xin
Abstract: In an effort to promote rational drug pricing and relieve the pressure of drug shortages, the Chinese government implemented a low‐price medicine (LPM) policy in July 2014, and abolished price regulations for most medications in June 2015. This study examines trends in the availability and pricing of LPMs since policy implementation. Data on price and availability of 752 LPMs during 2013–2017 were obtained from the Jiangsu Institute of Medicine Information. Availability was defined as the proportion of facilities in which a medicine was in inventory during each survey period. A price index was constructed based on purchasing prices in 40 public healthcare facilities, using a standard method developed by the International Labour Organization. Mean availability fluctuated slightly but held at low levels (<15%). Levels were conspicuously lower in primary hospitals than in secondary and tertiary hospitals. Our logistic regression model showed that the essential medicine designation was the main factor facilitating availability. The overall price index remained static before implementation of the policy, while there was a marked upward trend after implementation of the policy. Further efforts are needed to improve the pharmaceutical supply system, and simultaneously curb unreasonable inflation in medicine costs. Highlights: The Chinese government has cancelled government pricing regulations for medicines since June 2015. The ultimate objective of this government deregulation reform on drug prices is to the establish competitive markets, and drug prices determined by market forces. Excessively low pricing might reduce incentives for drug manufacturers to launch low‐price medicines (LPMs) into the market, leading to a shortage of medicines with advantages of low cost and high efficacy. In China, the reasons for low low‐price medicines availability may be multifactorial, and include inadequate funding, inefficient procurement systems, and insufficient incentives to maintain stocks. Further efforts are needed to improve the pharmaceutical supply system, and simultaneously curb unreasonable inflation in medicine costs.